Derecho natural y ciencia jurídica : consideraciones sobre la ciencia del derecho como ciencia práctica - Massini Correas, Carlos I. (Sapientia, 2007)
This paper deals with the vexata quaestio of the scientific character of legal science, to which the intention of being scientific and, at the same time, practical is contested. It tackles the contestings made, in this sense, by Claude Lévi-Strauss and Hans Albert, as well as the attempts made by some philosophers of law to improve it through the logical analysis of legal language. Later in the paper, the contributions made by some of the representatives of hermeneutic philosophy are analysed. They criticize analytic essays and suggest an interpretative understanding of legal science. The author, then, evaluates the analytic and hermeneutic contributions and highlights their strengths and weaknesses when it comes to establishing the scientific statute of legal science. He proposes an understanding of the science of law heir to the tradition of practical philosophy of Aristotelian stamp. In this regard, the author develops an analogical conception —based on Thomas Aquinas’thought— of scientific knowledge and explains in which way it is possible to apply it to a knowledge of law that proves to be, both, scientific and practical. Finally, he unwraps the epistemic need to refer legal science to, both, the first practical principles, studied by the doctrine of natural law, and to the most determined level of legal prudence.